2020
DOI: 10.1021/acs.jnatprod.9b01212
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Inhibits RANKL-Induced Osteoclastogenesis via Attenuating Akt, NF-κB, and PLCγ2-Ca2+ Signaling and Prevents Inflammatory Bone Loss

Abstract: The increase of bone-resorbing osteoclast activity in bone remodeling is the major characteristic of various bone diseases. Thus, inhibiting osteoclastogenesis and bone-resorbing function may be an effective therapeutic target for bone diseases. Betulinic acid (BA), a natural plant-derived pentacyclic triterpenoid compound, is known to possess numerous pharmacological and biochemical properties including anti-inflammatory, anticancer, and antiadipogenic activity. However, the effect of BA on osteoclast differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…Experimental durations less than 2 weeks generally consisted of two to three injections of LPS ranging from 5 to 10 mg/kg body weight per injection with bones collected for ex vivo analysis within 2 weeks of the first LPS exposure. This type of experimental design consistently demonstrated negative effects of LPS on trabecular bone structure, including BV/TV, Tb.N, and Tb.Sp, in the femur ( 42‐118 ) and tibia. ( 68,119‐124 ) In studies that reported negative effects of LPS exposure on trabecular bone structure, approximately half (22/47) also reported a decreased Tb.Th in the femur ( 48,55,59,70,77,81,88,89,94,97‐101,107,108,114,117,123 ) and tibia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental durations less than 2 weeks generally consisted of two to three injections of LPS ranging from 5 to 10 mg/kg body weight per injection with bones collected for ex vivo analysis within 2 weeks of the first LPS exposure. This type of experimental design consistently demonstrated negative effects of LPS on trabecular bone structure, including BV/TV, Tb.N, and Tb.Sp, in the femur ( 42‐118 ) and tibia. ( 68,119‐124 ) In studies that reported negative effects of LPS exposure on trabecular bone structure, approximately half (22/47) also reported a decreased Tb.Th in the femur ( 48,55,59,70,77,81,88,89,94,97‐101,107,108,114,117,123 ) and tibia.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental durations less than 2 weeks generally consisted of two to three injections of LPS ranging from 5 to 10 mg/kg body weight per injection with bones collected for ex vivo analysis within 2 weeks of the first LPS exposure. This type of experimental design consistently demonstrated negative effects of LPS on trabecular bone structure, including BV/TV, Tb.N, and Tb.Sp, in the femur ( 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ,…”
Section: Resultsmentioning
confidence: 99%
“…Despite this, no effects on endochondral growth were seen with addition of betulinic acid to metatarsal cultures. Other studies using bone cells in vitro have found that 10-15 µM and 10 mM betulinic acid induce bone formation by enhancing BMP2 [49], and inhibit osteoclastogenesis via RANKL [50], respectively. Herein, betulinic acid was used at 2.5 µM, which might be too low to exert any effects on endochondral growth in the context of an ex vivo organ culture system, which likely shows different requirements to cultured cells in vitro.…”
Section: Discussionmentioning
confidence: 91%
“…Betulinic acid (BA) is a pentacyclic triterpene compound that is derived from natural plants and is known to possess many pharmacological and biochemical properties, including anti-inflammatory and anti-cancer activities. Jeong et al (2020) found that BA inhibited RANKL-mediated intracellular levels of Ca 2+ through inhibition of PLCγ2 phosphorylation and reduced OCs production and bone resorption through the combined effect of Akt and NF-κB phosphorylation, and meanwhile BA reversed inflammatory bone loss induced by LPS injection in mice.…”
Section: Natural Plant Derivatives and Natural Compoundsmentioning
confidence: 94%